Understanding Intuitive Thinkingin the classroom of the 21st century learner - Arti Chopra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ushering in of 21st century has on one hand increased the challenges for the learners and on the other hand enhanced awareness of competencies & skills. With the emergent need to acquire optimum employability skills, outcome-based education is much in demand. Teachers and parents can give an eminent gift to their children by letting them adopt some supportive behaviors to enhance intuition.It is believed that intuition can pre-dominantly serve decision-making, problem-solving and creativity (Dane & Pratt,2009) as intuition can spontaneously generate ideas, alternatives or solutions (Sadler-Smith, 2004). Therefore, intuition seems indispensable to be used in teaching learning pedagogy. The extent to which one is able to access and utilize the non-conscious mind (Strick &Dijksterhuis, 2011), decides the effectiveness of intuition, and some experts argue that this can be enhanced (e.g.,Tomasino, 2011). Thispaper explores intuitive behavior of learner and teacher and an attempt to integrate strategies to enhance learning capacities. An attempt is made to view Intuition help teachers to sense pupils’ needs, engage more easily and effortlessly with them, and prevent conflicts.